Faith and Black-White Interracial Marriages : A Qualitative Research Study (Global Journal of Human-Social Science, 2013)
The landmark 1967 Loving vs Virginia Supreme Court ruling ended anti-miscegenation laws in America However the historic event did not change how interracial marriages were viewed from a societal standpoint Alonso 2000 Although such unions have increased in the 21st century problems associated with acceptance still abound Jayson 2011 The purpose of this qualitative research study is to explore how faith impacts Black-White Christian marriages Does it help these couples cope with adversity and or handle daily struggles better than those who do not share the same beliefs Or is there no significant difference at all William Gudykunst s 1995 Anxiety-Uncertainty Management Theory will serve as a theoretical framework for the study It contends the development of healthy interethnic relations and flexible interactions require a high degree of intergroup communication and in the same vein a heightened level of out-group communication Matusitz 2012 Ideas for further research will also be explored
Keywords: black-white interracial marriages; faith; struggles; further research